Dynamic non-coding RNA biomarker reveals lung injury and repair induced by polystyrene nanoplastics - Sheng Yang; Yiling Ge; Tianyi Zhang; Lihong Yin; Yuepu Pu; Zaozao Chen; Geyu Liang (Environment International)
Polystyrene nanoplastics (PS-NPs) are omnipresent in the air and can be inhaled by humans. However, their long-term adverse implications and toxicological mechanisms for human respiratory health are unclear. Therefore, this study aims to provide new insights into the pulmonary toxicity of PS-NPs using mice and organoid models. After subacute and subchronic inhalation of PS-NPs, mice showed pronounced lung injury characterized by respiratory rate changes, altered hematology, and histological evidence of tissue damage and oxidative stress. Similarly, repeated PS-NPs exposure also restricted organoid growth and cause oxidative damage. Notably, through BisqueRNA analysis for a single-cell dataset and canonical markers verification, it was found that PS-NPs induced the emergence and accumulation of transitional cells, suggesting impaired alveolar epithelial repair processes. Sequencing analyses revealed dynamic alterations in non-coding RNA (ncRNA) profiles, including circRNAs and lncRNAs, in response to PS-NPs exposure. Moreover, temporal profiling highlighted distinct sets of ncRNAs as early and progression-associated biomarkers of PS-NP-induced lung injury. These biomarkers correlated with aberrant transitional cells, implicating their roles in disrupted cellular differen tiation and repair mechanisms. Overall, this study observed the multifaceted toxicological responses of PS-NPs to the respiratory system, emphasizing the critical involvement of ncRNAs in mediating PS-NP-induce transitional cells, which was crucial for elucidating the pathophysiology of nanoplastic-induced lung injury and developing targeted therapeutic strategies.